205k views
2 votes
Simplify the product (x-4)(x+3)

2 Answers

2 votes

ANSWER


(x-4)(x+3) = {x}^(2) - x - 12

EXPLANATION

The given product is (x-4)(x+3)

We expand using the distributive property to obtain:


(x-4)(x+3) = x(x + 3) - 4(x + 3)

Expand the parenthesis to obtain:


(x-4)(x+3) = {x}^(2) + 3x- 4x - 12

Combine the similar terms to get:


(x-4)(x+3) = {x}^(2) - x - 12

User Niels Keurentjes
by
5.1k points
2 votes

Answer:

Final answer is
x^2-x-12.

Explanation:

Given expression is
\left(x-4\right)\left(x+3\right).

Now we need to find the product of the given expression
\left(x-4\right)\left(x+3\right).


\left(x-4\right)\left(x+3\right)


=x\left(x-4\right)+3\left(x-4\right)


=x^2-4x+3x-12

combine like terms


=x^2-1x-12


=x^2-x-12

Hence final answer is
x^2-x-12.

User Dmitry Negoda
by
5.7k points